2014
DOI: 10.1172/jci69004
|View full text |Cite
|
Sign up to set email alerts
|

Menin determines K-RAS proliferative outputs in endocrine cells

Abstract: R e s e a R c h a R t i c l e4 0 9 4 jci.org Volume 124 Number 9 September 2014 het; Figure 1B). We discovered that pancreata from E13.5 Kras-het embryos contained more endocrine cells, as determined by combined glucagon and insulin staining, than did WT pancreata, while overall pancreatic size remained unchanged (Figure 1, C-E, and Supplemental Figure 1; supplemental material available online with this article; doi:10.1172/JCI69004DS1). By P5, Kras-het animals had a relative expansion of both the glucagon-exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 57 publications
4
56
0
1
Order By: Relevance
“…Moreover, RASSF1A promoter methylation correlates with the worst prognosis in Ras driven tumors [20], and suppression of RASSF1A by shRNA promotes metastasis in mutant Ras cell lines [24]. In transgenic systems, RASSF1A loss enhances K-Ras induced proliferation [25]. …”
Section: Rassf1mentioning
confidence: 99%
“…Moreover, RASSF1A promoter methylation correlates with the worst prognosis in Ras driven tumors [20], and suppression of RASSF1A by shRNA promotes metastasis in mutant Ras cell lines [24]. In transgenic systems, RASSF1A loss enhances K-Ras induced proliferation [25]. …”
Section: Rassf1mentioning
confidence: 99%
“…These mouse models have shown that the expression of activated K-RAS(p.G12D) enhances rather than inhibits β-cell proliferation, β-catenin loss can suppress insulinoma tumorigenesis, histone demethylase retinoblastoma binding protein-2 (Rbp2) loss decreases insulinoma formation and prolongs survival, ActivinB loss prolongs survival, and MLL1/KMT2A loss leads to earlier onset of tumor formation (4 months vs. 6 months) and shortened lifespan by promoting tumor progression and angiogenesis (Chamberlain, et al 2014; Jiang, et al 2014; Lin, et al 2011; Lin, et al 2016; Ripoche, et al 2015). Such studies have dual benefits as they help to understand tumorigenesis and to reveal β-cell proliferation mechanisms for developing β-cell replacement strategies to help diabetic patients who suffer from functional β-cell loss (Garcia-Ocana and Stewart 2014).…”
Section: Genetically Engineered Mouse Modelsmentioning
confidence: 99%
“…Inhibition of MTOR with rapamycin reduces β-cell proliferation (15,2933), but genetic manipulation of MTOR leads to less clear results, with some studies suggesting that MTOR drives β-cell proliferation (15,3437) and others not (3841). ERK, activated by glucose in β-cells (12), is proproliferative in other cell types but may play a paradoxical antiproliferative role in β-cells (42,43). …”
Section: Introductionmentioning
confidence: 99%